Entre el arte sonoro y la música: panorama en Colombia (2023)
The aim of this article is to present an overview of music in the contexts of sound art in Colombia, from its confluences and controversies in environments of creation, circulation and formation. A mixed work of compilation, systematization and classification of works on sound art that have taken place in Colombia since the nineties, and the conceptions of sound artists in the country, was carried out in order to present a general perspective and the state of the current discussion on the object of study. Throughout the text, we will observe the imprint that music has on sound art production, its influence on creation, its permanent participation in festivals, exhibitions and concerts of sound art and the representation in the formative processes that universities have been contributing to the subject. In addition, the tensions generated by the exercise of its definitions, the recognition of the disciplinary limits imposed by tradition and the concepts of matter, space and time that border both disciplines will be discussed. The research reveals the importance of pursuing the task of systematizing and characterizing the practices of sound art in the country, in order to build a history that must be told in its particular Colombian context.